Effectiveness Educational Programme on Knowledge Towards Management of Neonatal Infection Among Post Natal Mothers.” - Shete, Sushama s (International Journal of Psychosocial Rehabilitation, 2020)
Children are future and almost precious resources. Newborns especially, prematurely can without much of a stretch become tainted previously, during and after birth. Infection and newborn sepsis management reduce the opportunity for infection and improved intrapartum practices. Neonatal contaminations might be shrunk by mother to youngster transmission, in the birth waterway during labor, or contracted after birth. Objectives: To assess knowledge on management of neonatal infection among post natal mothers, To assess the adequacy of educational program on management of neonatal infection among post natal mothers, To find out an association between the selected demographic variables, pre and post- test. Methods: For this study Evaluative research approach was used. Quasi experimental research design was utilized.. Study was conducted on 50 subjects from NICU of Krishna Hospital, Karad. Using Non Probability Convenient sampling technique .The data was collected using pre tested self administered questionnaire. Frequency distribution analysis was performed. Result: Among 50 postnatal mothers Maximum number 56 % of mothers belonged to age of 20-25 year. Majority of samples 78 % were from Hindu religion.34%mothers were educated up to Secondary School, 74%mothers were housewives, 38% mothers family income5000-10,000/month and 74% mothers were from joint family ,100% mothers had no any bad habit 56%mothers were from rural family. In the pre test 64%mothers having average knowledge and in the post 94% mothers had good knowledge. The pre mean score is 9.46; post test mean is 21.7.and t value is 17.46. After the association of masterminded training the pretest and posttest information investigation uncovered that mean post score was higher than the mean pretest score. Conclusion: Study reasoned that the instructive program was effective in terms of gain in knowledge regarding management of neonatal infection among post natal mothers.